Introduction to No. 1: Ecophilosophical and Biopolitical Challenges. Past and Future - Dzwonkowska, Dominika (ETHICS IN PROGRESS, 2016)
Introductory remarks to Ethics in Progress Special Issue, Vol. 7(2016) No. 1.